governance for disaster risk reduction: government service recovery in flood disaster: Case of Kelantan flood prone area. - Mokhtar, Khairiah Salwa (Universiti Sains Malaysia, 2016)
The December 2014 flood was considered the worst unexpected natural disaster in Malaysia. Kelantan, Terengganu and Pahang were the three states which were affected the most. Infrastructures and basic facilities including electrical and communication system as well as transportation network were badly affected. Thousands of victims were evacuated and rescued to safer places. This alarming situation had denied the victims from receiving immediate aids of various different forms from several sources.